1990
DOI: 10.1001/archotol.1990.01870080042012
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatization of the Paranasal Sinuses (Maxillary and Frontal) in Cleft Lip and Palate

Abstract: A comparative study of roentgenograms of the paranasal sinuses between 37 patients with cleft lip and palate and 37 control subjects of the same age group was done using a planimeter. The results indicate that there is no statistical difference in the sizes. The paranasal sinuses increased in size with age in patients as well as in control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
9

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 6 publications
0
28
0
9
Order By: Relevance
“…Notwithstanding that development and growth of the maxillary sinus are closely related to the growth of the skull and to the dentition (Wolf et al, 1993), it has been demonstrated that the sinuses also possess a developmental potential of their own (Libersa et al, 1991;Koppe et al, 1994). On the other hand, recent studies by Francis et al (1990) and Oktay (1992), who have revealed that neither cleft lip and palates nor orthodontic malocclusion affect the size of the maxillary sinus, give some doubts about an exclusive structural role of the paranasal sinuses. To strengthen this assumption further analyses in a wide range of non-human primates are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding that development and growth of the maxillary sinus are closely related to the growth of the skull and to the dentition (Wolf et al, 1993), it has been demonstrated that the sinuses also possess a developmental potential of their own (Libersa et al, 1991;Koppe et al, 1994). On the other hand, recent studies by Francis et al (1990) and Oktay (1992), who have revealed that neither cleft lip and palates nor orthodontic malocclusion affect the size of the maxillary sinus, give some doubts about an exclusive structural role of the paranasal sinuses. To strengthen this assumption further analyses in a wide range of non-human primates are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of clinical studies leave some doubt about a significant relationship between MS size and craniofacial shape, even in case of congenital malformation of the palate. Although patients with cleft palates suffer more frequently from sinusitis, it is interesting that the postnatal growth patterns of the paranasal sinuses of those patients do not significantly differ from unaffected populations [Robinson et al, 1982;Francis et al, 1990]. Indeed, a recent study involving human fetuses suggests a similar timing of sinus formation in both normal fetuses and fetuses with cleft lip and palate [Smith et al, 1999].…”
Section: Implication Of Craniofacial Growth On Skull Pneumatization Imentioning
confidence: 99%
“…A significant anatomic variation could demonstrate a potential factor in the higher frequency of sinus disease among patients with cleft. Previous studies evaluated the area of maxillary sinuses of CLP patients using such different imaging modalities as conventional radiographs and multi-slice computed tomography (MSCT) [2,4,5,[8][9][10]. However, the area estimation is a two-dimensional (2D) assessment of a three-dimensional (3D) structure, therefore potentially limited and prone to error.…”
Section: Introductionmentioning
confidence: 99%